The serum level of C-reactive protein (CRP) is associated with cognitive performance in acute phase psychosis. Issue 1 (December 2016) - Johnsen, Erik; Fathian, Farivar; Kroken, Rune; Steen, Vidar; Jørgensen, Hugo; Gjestad, Rolf; Løberg, Else-Marie
Abstract Background Inflammatory processes have been implicated in the etiology of schizophrenia and related psychoses, in which cognitive deficits represent core symptoms. The aim of the present study was to investigate possible associations between the level of the inflammation marker C-reactive protein (CRP) and cognitive performance in patients through the acute phase of psychosis. Methods A total of 124 patients were assessed at admittance to hospital and 62 patients were retested at discharge or after 6 weeks at the latest, with measurements of the CRP levels and alternative forms of the Repeatable Battery for the Assessment of Neuropsychological Status. Results There was an inverse relationship between overall cognitive performance and CRP level at admittance. The association increased in sub-analyses including only patients with schizophrenia. In cognitive subdomain analyses statistically significant inverse associations were found between the CRP level and Delayed memory and Attention, respectively. No associations were found between CRP level and other measures of psychopathology including psychosis symptoms, depression, or functioning. At follow-up the association between CRP level and cognition was no longer present. There was a significant increase in cognitive performance between baseline and follow-up. There was a stronger increase in overall cognition scores in patients with higher baseline CRP levels. Conclusions The findings indicate that signs of inflammation may serve as a state-dependent marker of cognitive dysfunctions in acute psychosis. Trial registration ClinicalTrials.gov ID;NCT00932529, registration date: 02.07.2009